Microeconomics [5th ed.] - Pindyck, Robert S.; Rubinfeld, Daniel L. (Prentice Hall New Jersey, 2001)
The market leader in Intermediate Microeconomics, the book is well known for its coverage of modern topics (Game theory, Economics of Information), clarity of its writing style and graphs, and integrated use of real world examples. The book is used in both economics departments and business schools and is well received for its applied nature. The emphasis on relevance and application to both managerial and public-policy decision making are focused goals of the book. It succeeds in showing how microeconomics can be used as a tool for decision making.
Keywords: Microeconomics; Equilibrium and economic efficiency